2021
DOI: 10.3390/pr9040617
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Microplastics Removal from Wastewater Using Electro-Coagulation and Granule-Activated Carbon with Thermal Regeneration

Abstract: Discharge from sewage treatment plants (STPs) is a significant pathway of entry for microplastics (MPs) to the environment. Therefore, STPs should be considered as an important barrier to the distribution and circulation of MPs in the aquatic environment. In this study, the fate and material-specific properties of MPs were investigated in an STP-equipped and granule-activated carbon (GAC) tower with a thermal regeneration system. This system functioned with a tertiary treatment unit. The GAC with thermal regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…These compounds are lighter than water, which is rarely removed in primary and biological treatments. About MP removal efficiency, similar results were obtained for the DWTP (drinking water treatment plant) equipped with the GAC filtration system (88% cumulative removal) [ 101 ]. Moreover, adsorbents prepared from plastic waste without the addition of any environmental-related problematic raw materials or products have gained much attention.…”
Section: Different Technologies and Approaches For The Removal Of Pla...supporting
confidence: 64%
See 1 more Smart Citation
“…These compounds are lighter than water, which is rarely removed in primary and biological treatments. About MP removal efficiency, similar results were obtained for the DWTP (drinking water treatment plant) equipped with the GAC filtration system (88% cumulative removal) [ 101 ]. Moreover, adsorbents prepared from plastic waste without the addition of any environmental-related problematic raw materials or products have gained much attention.…”
Section: Different Technologies and Approaches For The Removal Of Pla...supporting
confidence: 64%
“…Kim et al [ 101 ] investigated worms that can consume polystyrene to a strain of bacteria that lives in the larvae’s gut. They placed polystyrene as the only carbon source with 50 superworms in a chamber and observed that the worms had consumed around 70% of the plastic in the first 21 days.…”
Section: Different Technologies and Approaches For The Removal Of Pla...mentioning
confidence: 99%
“…While EC has been a well-studied area of research, there are relatively few studies specifically focused on MPs removal. These studies indicate that EC could effectively remove MPs, i.e., more than 90% removal in optimum reaction conditions from real wastewater [92][93][94][95] and artificial wastewater [77,96].…”
Section: New Developmentsmentioning
confidence: 80%
“…They focused on the removal of various types of PTFE plastics using an aluminum electrode. The authors achieved more than 90% removal efficacy by electrocoagulation of particles that could not be removed with other methods [47].…”
Section: Coagulation/flocculationmentioning
confidence: 98%